Penerapan Terapi Relaksasi Tarik Nafas dalam untuk Mengurangi Ansietas Pasien Intradyalitic dengan Gagal Ginjal Kronis: Studi Kasus - Fidia Az-Zahra; Dwiyanti Purbasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Chronic Kidney Disease (CKD) is a progressive health problem that often requires long-term hemodialysis therapy. The hemodialysis process may cause psychological problems, particularly anxiety, which can affect treatment adherence, emotional well-being, and quality of life. Deep breathing relaxation therapy is a non-pharmacological nursing intervention that can help reduce anxiety and promote relaxation. Objective: To describe the implementation of deep breathing relaxation therapy in reducing anxiety among intradialytic patients with chronic kidney disease. Methods: This study employed a case study approach using the nursing care process, including assessment, nursing diagnosis, planning, implementation, and evaluation. Deep breathing relaxation therapy was administered during hemodialysis sessions, and anxiety levels were evaluated before and after the intervention using appropriate anxiety indicators. Results: The implementation of deep breathing relaxation therapy showed a reduction in patients’ anxiety levels. Patients appeared calmer, were able to control anxious feelings more effectively, demonstrated improved emotional responses, and reported greater comfort during hemodialysis procedures. Implications: Deep breathing relaxation therapy is a simple, safe, and effective non-pharmacological nursing intervention for reducing anxiety in patients with chronic kidney disease undergoing hemodialysis. This intervention may improve patient comfort, support psychological well-being, and enhance the quality of holistic nursing care.